PCR-based methods for identification of Enterococcus species - Drahovská, H; Kocíncová, D; Seman, M; Turna, J (Folia microbiologica, 2002)
Two DNA-based techniques were used for species identification of enterococci. PvuII digestion of the genus-specific PCR product yielded four different restriction profiles among 20 enterococcal species; one of them was species-specific for E. faecium. In the second case, 32 reference strains belonging to 20 enterococcal species were divided to 12 groups by amplification of internal transcribed spacer of rRNA operon. Interspecies and some intraspecies profile variability was determined. Both methods gave similar results.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; protozoální DNA; druhová specificita; intergenová DNA; DNA, Protozoan; Enterococcus; DNA, Intergenic; restrikční endonukleasy typu II; Deoxyribonucleases, Type II Site-Specific; Species Specificity